2023
DOI: 10.1111/jog.15562
|View full text |Cite
|
Sign up to set email alerts
|

Acute uterine inversion following an induced abortion

Abstract: Acute uterine inversion is a rare and potentially life‐threatening obstetric emergency. Its occurrence as a result of a mid‐trimester abortion is an even rarer consequence. We report a case of a 32‐year‐old woman who presented with complete acute uterine inversion and hemorrhagic shock following an incomplete medical abortion at 14 weeks of gestation. Our attempts at non‐operative reversal of the inversion failed. Therefore, we resorted to the manual replacement of the uterus via laparotomy without using surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A 14-year retrospective study suggests that transabdominal ultrasound confirmation of placental abruption may help prevent postpartum uterine inversion. [23] If these measures are ineffective, immediate surgical repositioning should be performed, including open manual repositioning, [24,25] laparotomy, and laparoscopic surgery. Operative procedures used include Huntington procedure, Haultain procedure, Kustner approach, etc, and some patients may need to undergo hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 14-year retrospective study suggests that transabdominal ultrasound confirmation of placental abruption may help prevent postpartum uterine inversion. [23] If these measures are ineffective, immediate surgical repositioning should be performed, including open manual repositioning, [24,25] laparotomy, and laparoscopic surgery. Operative procedures used include Huntington procedure, Haultain procedure, Kustner approach, etc, and some patients may need to undergo hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…If these measures are ineffective, immediate surgical repositioning should be performed, including open manual repositioning, [24,25] laparotomy, and laparoscopic surgery. Operative procedures used include Huntington procedure, Haultain procedure, Kustner approach, etc, and some patients may need to undergo hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…
Dear Editor, Swarray-Deen et al 1 reported manual repositioning of acute uterine inversion under laparotomy. After repositioning, acute reinversion sometimes occurs.
…”
mentioning
confidence: 99%